THE USE OF ACTIVE SCAFFOLDING IN EFL WRITING CLASS - Kanditha Kharisma Wijaya (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2019)
The objectives of the research are : to find out whether Active Scaffolding can enhance students’ writing skill on narrative text and to find out the implementation of Active Scaffolding in teaching and learning writing at the eight grade students of SMPN 27 Surakarta in 2018/2019 Academic Year especially in class VIII C. The research was carried out at SMPN 27 Surakarta. It was conducted from August up to september 2018 The subject of the research was the students of eight grade. In implementation of the teaching and learning process, the researcher divided the research into two cycle. Cycle 1 into 2 meeting and cycle 2 into 2 meeting with post test in every cycle. Every cycle consists of 3 steps; exploration, elaboration, and confirmation. In collecting data, the reseacher used qualitative and quantitative data. The qualitative data consisted of observation, interview and questionare. The quantitative data consisted in Pre-Test, Post-Test 1 and Post Test 2. The result of Cycle 1 showed that some students still less on grammar, and vocabulary. Therefore, Cycle II showed that the use of Active Scaffolding from content, organization, language use, vocabulary and mechanic are effective to enhance the students’ writing skill. The findings are supported by the qualitative data of students’ responses in field note, interview and questionare. The quantitative data enhanced from pre-test to post test 1 and post test 2. The students’ mean score in pretest was 43,20, post test 1 was 60,00 and post test 2 was 70,74. Based on the result of the data from pre test, post test and questionare, it could be concluded that “The use of Active Scaffolding can improve students’ writing skill on narrative text, and how far the implementation of Active Scaffolding in teaching and learning writing at the eight grade students of SMPN 27 Surakarta in 2018/2019 academic year especially in class VIII C ”. Key word: Writing Skill, Active Scaffolding, Classroom Action Research, Narrative Text.